Impact of hygrothermal aging on rotational behavior of web-flange junctions of structural pultruded composite members for bridge applications. (1st February 2017) - Xin, Haohui; Mosallam, Ayman; Liu, Yuqing; Wang, Congzhe; Zhang, Youyou
Abstract: This paper presents the results of the second part of a multi-phase study focused on hygrothermal behavior of pultruded fiber reinforced polymer (PFRP) web-flange junction for bridge applications. The information reported herein focuses on hygrothermal effect on the rotational stiffness and strength of web/flange junctions (WFJs) of typical pultruded profiles commonly used in general construction applications and in bridge decks in particular. Experimental results extracted from a total of twenty-seven as-built (unexposed) and seventy-six pultruded WFJs specimens exposed to fresh water and artificial seawater environments at temperatures of 40 °C, 60°Cand 80 °C. The study evaluated the rotational characteristics of six different web-flange junctions and hygrothermal aging effects on one of such junctions. The experimental results indicated that the moment capacity and associated rotational stiffness of J1 junction group specimens was the largest among the junction "J" groups evaluated in this study. In addition, it was concluded that the rotation moment and rotation stiffness of J1 junction are largest among junction "J" group, the rotation moment of AJ2-M1 junction is largest but the rotation stiffness of AJ3-M1junction is largest among "AJ#-M1" group and the rotation moment and rotation stiffness of AJ3-M2 junction is largest among "AJ#-M2" group. A general conclusion was reached, based on the experimental results, that is both the WFJ moment capacity and associated rotational stiffness are proportional to the size of three factors: (i) web thickness, (ii) fillet radius, and (iii) flange thickness of the pultruded profile. Results also showed that: 1) the difference in ultimate moment capacity degradation due to hygrothermal effects for WFJs exposed to fresh water and artificial seawater environments at temperatures of 40 °C and 80 °C is relatively small, however, the ultimate moment capacity degradation of specimens exposed to artificial seawater was relatively higher as compared to those exposed to fresh water environments at a temperature of 60 °C; 2) in general, exposure to higher temperatures, results in a relatively higher strength degradation, except for the case of fresh water exposure at temperatures of 40°C and 60 °C.